Fiscal multipliers and policy coordination - Gauti B. Eggertsson (Federal Reserve Bank of New York, 2006)
This paper addresses the effectiveness of fiscal policy at zero nominal interest rates. I analyze a stochastic general equilibrium model with sticky prices and rational expectations and assume that the government cannot commit to future policy. Real government spending increases demand by increasing public consumption. Deficit spending increases demand by generating inflation expectations. I derive fiscal spending multipliers that calculate how much output increases for each dollar of government spending (real or deficit). Under monetary and fiscal policy coordination, the real spending multiplier is 3.4 and the deficit spending multiplier is 3.8. However, when there is no policy coordination, that is, when the central bank is “goal independent,” the real spending multiplier is unchanged but the deficit spending multiplier is zero. Coordination failure may explain why fiscal policy in Japan has been relatively less effective in recent years than during the Great Depression.
Keywords: E52; E63; 330; policy coordination; fiscal multiplier; zero interest rates; deflation; Finanzpolitik; Geldpolitik; Wirtschaftspolitisches Ziel; Allgemeines Gleichgewicht; Preisrigidität; Theorie; Koordination